Studying Interactions by Molecular Dynamics Simulations at High Concentration. (22nd February 2012) - Fogolari, Federico; Corazza, Alessandra; Toppo, Stefano; Tosatto, Silvio C. E.; Viglino, Paolo; Ursini, Fulvio; Esposito, Gennaro
Abstract : Molecular dynamics simulations have been used to study molecular encounters and recognition. In recent works, simulations using high concentration of interacting molecules have been performed. In this paper, we consider the practical problems for setting up the simulation and to analyse the results of the simulation. The simulation of beta 2-microglobulin association and the simulation of the binding of hydrogen peroxide by glutathione peroxidase are provided as examples.